Menghadapi Stres Akademik: Solusi dari Perspektif Teologi Kristen untuk Mahasiswa - Intan Meida Sari Gea; Korina Sanosa; Ridwan Bangun; Amoli Ndraha (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The academic world is an important focus in doing assignments, which is a process that is full of obstacles because there are many challenges that students must go through while working on it. In Indonesia, there has been a threat to the well-being of students in the form of academic stress and there are various cases of the consequences of this pressure. This article aims to outline the importance of overcoming student stress in the academic field, as well as efforts to overcome the problem based on a biblical perspective on stress. Qualitative method with analytic descriptive approach, which explains the situation under study in detail through descriptive presentation. Qualitative research methods through literature studies related to